2022
DOI: 10.3390/plants11182430
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Leaching Mitigation Options in Two Dairy Pastoral Soils and Climatic Conditions in New Zealand

Abstract: This lysimeter study investigated the effect of late-autumn application of dicyandiamide (DCD), co-poly acrylic-maleic acid (PA-MA), calcium lignosulphonate (LS), a split-application of calcium lignosulphonate (2LS), and a combination of gibberellic acid (GA) and LS (GA + LS) to reduce N leaching losses during May 2020 to December 2020 in lysimeter field sites in Manawatu (Orthic Pumice soil) and Canterbury (Pallic Orthic Brown soil), New Zealand. In a second application, urine-only, GA only and GA + LS treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…On the other hand, the high rainfall events and intensity between June and September may have leached the GA into the soil. Similar results of GA showing a nominal reduction in NO 3 − -N leaching have been reported in other studies [11,16]. The authors demonstrated that application of urine + GA alone in mid-winter did not induce a significant reduction in mineral N leaching in lysimeter studies.…”
Section: Nitrate-n Leachingsupporting
confidence: 86%
See 3 more Smart Citations
“…On the other hand, the high rainfall events and intensity between June and September may have leached the GA into the soil. Similar results of GA showing a nominal reduction in NO 3 − -N leaching have been reported in other studies [11,16]. The authors demonstrated that application of urine + GA alone in mid-winter did not induce a significant reduction in mineral N leaching in lysimeter studies.…”
Section: Nitrate-n Leachingsupporting
confidence: 86%
“…Three soil cores in each 0.2 m 2 urine patch were collected to 30 cm depth during harvesting at each experimental site using a stainless-steel corer with an internal diameter of 3 cm. Field moist soil cores from each treatment were composited and mixed manually before a 5 g sub-sample was extracted using 30 mL of 2 M KCl for mineral N (NH 4 + -N and NO 3 − -N) analysis on an end-over shaker for 1 h [11]. Extractants were analyzed for mineral N using the Technicon autoanalyzer [12].…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
See 2 more Smart Citations